Observation of the subgap optical absorption in polymer-fullerene blend solar cells - Goris, L.; Poruba, A.; Hod'ákova, L.; Vaněček, M.; Haenen, K.; Nesládek, M.; Wagner, P.; Vanderzande, D.; De Schepper, L.; Manca, J. V. (Applied physics letters, 2006)
This letter reports on highly sensitive optical absorption measurements on organic donor-acceptor solar cells, using Fourier-transform photocurrent spectroscopy (FTPS). The spectra cover an unprecedented dynamic range of eight to nine orders of magnitude making it possible to detect defect and disorder related sub-band gap transitions. Direct measurements on fully encapsulated solar cells with an active layer of poly[2-methoxy-5-( 3 ′ , 7 ′ -dimethyl-octyloxy)]-p-phenylene-vinylene:(6,6)-phenyl-C61-butyric-acid (1:4 weight ratio) enabled a study of the intrinsic defect generation due to UV illumination. Solar cell temperature annealing effects in poly(3-hexylthiophene):PCBM (1:2 weight ratio) cells and the induced morphological changes are related to the changes in the absorption spectrum, as determined with FTPS.